À la recherche de la forme et du sens des gestes quasi-linguistiques et syllinguistiques dans la communication française, italienne et polonaise - Szarota, Beata (AMU Press, 2010)
The present paper is an attempt supplying proofs that gestural signs are almost like standard linguistic signs. It is claimed that language gestures exhibit numerous properties of classical linguistic signs conceived of as in the works of de Saussure. The dividing line between the two pertains, in essence, to the type of motivation between the signifier and the signified, found within gestural, but not linguistic signs. There is a conspicuous connection between the two aspects of the sign within various kinds of gestures, including volitional ones (most akin to speech acts or „la parole” of the Saussure) as well as within those which are not performed on purpose (called „sylinguistic” gestures).
Keywords: linguistic signs; expressive gestures